Bone Mineral Density is Unaltered in Women with Polycystic Ovary Syndrome - Ganie, Mohd Ashraf; Chakraborty, Semanti; Sehgal, Ashish; Sreejith, M.; Kandasamy, Devasenathipathy; Jana, Manisha; Rashid, Aafia (Hormone and Metabolic Research, 2018)
Context The effects of endocrine aberrations associated with polycystic ovary syndrome (PCOS) on bone mineral density (BMD) in young women is a matter of debate.Objectives To compare BMD in young women with PCOS to age and body mass index (BMI) matched controls and to elucidate its correlation to BMI, insulin resistance and serum testosterone.Design and Methods We recruited 60 women with PCOS aged 14-24 years, diagnosed based on Rotterdam 2003 criteria, and 58 age matched controls. BMD was measured by dual energy X-ray absorptiometry. In addition, these subjects underwent biochemical and hormonal analysis including oral glucose tolerance test, calculation of Homeostatic Model Assessment–Insulin Resistance Index, measurement of serum thyroxine, thyrotropin, prolactin, total testosterone, dehydroepiandrosterone sulfate, follicular phase luteinizing hormone and follicle stimulating hormone.Results There was no difference of BMD between women with PCOS and control women (1.103±0.08 vs 1.126±0.083 g/cm2; p=0.122). In subgroup analysis based on BMI, BMD in obese women with PCOS was significantly higher than their overweight and lean counterparts at lumbar spine (p<0.001), neck of femur (p=0.005) and total hip (p<0.001). BMD was not different at any site between oligomenorrheic and non-oligomenorrheic women with PCOS. It positively correlated with BMI, waist and hip circumference in women with PCOS. No correlation was found with HOMA-IR or Testosterone.Conclusions BMI is the most important determinant of BMD in women with PCOS. BMD is not different between healthy young women and those with PCOS.
Keywords: polycystic ovary syndrome; bone mineral density; dual energy X-ray absorptiometry; adolescent women; body mass index